Reconfigurable Photonic Lattices Based on Atomic Coherence - Yuan, Jiaqi; Liang, Shun; Yu, Qingsong; Li, Changbiao; Zhang, Yanpeng; Xiao, Min; Zhang, Zhaoyang (Advanced Physics Research, 2025)
The array of coupled optical waveguides, which is also viewed as a photonic lattice, can exhibit abundant photonic band structures depending on the desired spatial arrangements of involved waveguides. Studies of photonic lattices are usually performed in solid‐state materials, where the required periodic susceptibilities can be achieved by employing the femtosecond laser direct‐writing or optical induction method, and have spawned flourishing achievements in manipulating the behaviors of light. Recently, the concept of electromagnetically induced photonic lattice (EIPL) is proposed under the well‐known electromagnetically induced transparency (EIT) in coherently prepared multilevel alkali‐metal atomic systems, where the strong coupling beams producing EIT possess spatially periodic intensity profiles. The inherited instantaneous tunability of susceptibility from EIT‐modulated atomic coherence allows for the easy reconfigurability of EIPLs, which gives rise to exotic beam dynamics under such a readily controllable framework. This paper summarizes the historical overview and recent advances of the in situ and all‐optically reconfigurable EIPLs. The Introduction section provides the scheme and formation of the EIPL via atomic coherence. The following sections review the recently demonstrated dynamical properties of light in various 1D and 2D EIPLs and in compound EIPLs built by two coupling fields. The final section gives brief concluding remarks. Thermal atomic vapors are employed to effectively establish various instantaneously reconfigurable photonic lattices, with the assistance of electromagnetically induced transparency excited by a spatially periodic strong coupling field. Such electromagnetically induced photonic lattices with in situ tunability have served as a fertile ground for exploring the exotic beam dynamics arising from the interactions between light and desired band structures.